ACTL6A: unraveling its prognostic impact and paving the way for targeted therapeutics in carcinogenesis - Eid, Refaat A.; Mamdouh, Farag; Abdulsahib, Waleed K.; Alshaya, Dalal Sulaiman; Al-Salmi, Fawziah A.; Ali Alghamdi, Maha; Jafri, Ibrahim; Fayad, Eman; Alsharif, Ghadi; Zaki, Mohamed Samir A.; Alshehri, Mohammed A.; Noreldin, Ahmed E.; et al. (Frontiers in Molecular Biosciences, 2024)
Introduction: Increased Actin-like 6A (ACTL6A) expression is associated with various cancers, but its comprehensive investigation across different malignancies is lacking. We aimed to analyze ACTL6A as a potential oncogene and therapeutic target using bioinformatics tools. Methods: We comprehensively analyzed ACTL6A expression profiles across human malignancies, focusing on correlations with tumor grade, stage, metastasis, and patient survival. Genetic alterations were examined, and the epigenetic landscape of ACTL6A was assessed using rigorous methods. The impact of ACTL6A on immune cell infiltration in the tumor microenvironment was evaluated, along with molecular docking studies and machine learning models. Results: Our analysis revealed elevated ACTL6A expression in various tumors, correlating with poor prognostic indicators such as tumor grade, stage, metastasis, and patient survival. Genetic mutations and epigenetic modifications were identified, along with associations with immune cell infiltration and key cellular pathways. Machine learning models demonstrated ACTL6A's potential for cancer detection. Discussion: ACTL6A emerges as a promising diagnostic and therapeutic target in cancer, with implications for prognosis and therapy. Our study provides comprehensive insights into its carcinogenic actions, highlighting its potential as both a prognostic indicator and a target for anti-cancer therapy. This integrative approach enhances our understanding of ACTL6A's role in cancer pathogenesis and treatment.